Aesthetic and dramatic dimensions of silence in the feature film (Al-Academy, 2017)
Which was entitled : Aesthetic and dramatic dimensions of silence in the feature film , and the researcher clearly define after removing the confusion existing in some authorized sources , as for the concept of silence , adopted in this research is : the death of the audio stream , Hence the researcher shed a light on the aesthetic and the dramatic role of silence in the feature film , through the handing of the silent scenes ( absolute silence ) in the film research divided this research into four chapters . This first Chapter includes : methodological framework , which represents the research problem , which came with the following question : what is the mechanism of productive silence to the aesthetic and dramatic dimensions in the feature film ? The goal was determined to reveal about :1- The real concept of the silence used in the film . 2 - The aesthetic and dramatic dimensions of silence in the feature film . The second chapter includes the theoretical framework ; the first research topic which covers the concept of silence , the second topic is about the mechanism of operating the silence in the theoretical framework . The third chapter included search procedures , and also included the methodology and performance of the research as theoretical indicators which came from the theoretical framework . The research sample included the feature film (Alresala – The message ) in Arabic version for Mustafa Al – Aqad as director . The fourth chapter included analysis and results .